2019
DOI: 10.2147/jpr.s205561
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparisons of the efficacy and recurrence of adenomyomectomy for severe uterine diffuse adenomyosis via laparotomy versus laparoscopy: a long-term result in a single institution</p>

Abstract: Purpose Studies have shown that adenomyomectomy can effectively treat women with adenomyosis in a short period of time. However, the long-term efficacy of adenomyomectomy has rarely been reported. The objective of this study was to determine whether laparotomy is superior to laparoscopic surgery in the long-term efficacy of double-flap method adenomyomectomy for severe diffuse adenomyosis. Methods Between March 2011 and September 2018, a total of 148 patients with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…In our study, patients in both groups showed a lower rate of relapse (n = 1, 1.39% vs. n = 1, 1.35%) than previously reported (n = 32, 28.1%) 20 at the end of the 2-year follow-up period. These results are consistent with those reported previously by Zhu et al 22 . In our study, we found that the double/multiple-flap method could remove adenomyomatic lesions more radically and could reduce the risk of recurrence over time, at least theoretically.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, patients in both groups showed a lower rate of relapse (n = 1, 1.39% vs. n = 1, 1.35%) than previously reported (n = 32, 28.1%) 20 at the end of the 2-year follow-up period. These results are consistent with those reported previously by Zhu et al 22 . In our study, we found that the double/multiple-flap method could remove adenomyomatic lesions more radically and could reduce the risk of recurrence over time, at least theoretically.…”
Section: Discussionsupporting
confidence: 94%
“…The LNG-IUD releases 20 mg of levonorgestrel each day and represents an effective treatment for adenomyosis [21]. Zhu et al [22] further reported that the recurrence rate was significantly higher in patients who were only treated with GnRHa after surgery than in patients who were treated with GnRHa plus LNG-IUS after surgery (51.6 vs. 8.3 %; p < 0.05). In our study, patients in both groups showed a lower rate of relapse (n = 1, 1.39 % vs. n = 1, 1.35 %) than previously reported (n = 32, 28.1 %) [20] at the end of the 2-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that of those who received 6 courses of GnRH‐a after laparoscopic adenomyomectomy, 11.5% experienced relapse compared with 39.1% experienced relapse in the surgical‐only treatment group, 20 but with a high recurrence rate after drug discontinuation 21 . Zhu et al 22 . reported that significant differences of the recurrence rate were found between patients with adenomyosis who were only treated with GnRH‐a postoperatively and patients who were treated with GnRH‐a plus LNG‐IUS after surgery (33.3% vs 5.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The first case could explain why up to 50% of patients who underwent surgical EM resection, have a recurrence of complaints and "new" EM lesions within 5 years [24,25]. The opinion of Kahn et al that OME lesions are biologically active and have growth potential would support this theory [22].…”
Section: The Meaning Of Omementioning
confidence: 99%